Pakistan in the Twentieth Century : A Political History - Ziring, Lawrence, 1928- (Karachi Oxford University Press, 2005)
Unlike other available works on the political history of Pakistan, the present volume is wholly comprehensive covering both the pre-independence Pakistan nationallist movement as well as detaining events in the fifty years since independence.
Include Bibliography and Index
Keywords: Politics and government